Social Stockholm Syndrome: The Sample of Jews - Kerem Tarık Şahiner (Burdur İlahiyat Dergisi)

(untitled)
Stockholm syndrome is defined as the development of an emotional attachment by a captive or prisoner to his or her captor. In this context, the hostage feels an attachment to the hostage taker. This term originated in a bank robbery in the city of Stockholm when one of the hostages was unable to separate from the robber after the robber released him. The hostage was involved in the crime as a voluntary part of the robbery. This theme, which is treated individually in psychology, has a social and historical dimension in the case of the Israelites. What we mean by the conceptualisation of "Social Stockholm Syndrome" is the attempt to explain the social reflexes such as admiration and imitation developed by the lower stratum society against the upper stratum society after the societies, like individuals, have been in a second class position under the hierarchical superiority of another society at any time in history, tortured, enslaved or enslaved.